Clinicopathological analysis of ovarian tumors: a two year retrospective study - Chandra, Kanika; Arora, Neetu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Ovarian tumours are a heterogeneous neoplasm with a varied clinical, morphological and histological feature. Increasing mortality rate due to ovarian cancers has been reported in recent years. Ovarian tumours in post-menopausal females have high risk of malignancy and it has a very poor outcome. The aim and objective of this study was to determine clinical and histopathological spectrum and the frequency and age distribution of various ovarian tumors. Methods: It is a retrospective observational study of patients with ovarian tumors in the department of obstetrics and gynecology, SGRRI of Medical Health & Sciences and Hospital from January 2016 to December 2017 in a total number of 86 patients. All specimens were sent to pathology department and categorised according to WHO hispathological classification. Results: Out of 86 cases examined, 64 cases were benign (74.4%), 3 cases were borderline (3.4%) and 19 cases were malignant (22.2%). Majority of the ovarian tumors (73.4%) were seen in the age group of 20 to 50 years. Most commonly encountered benign ovarian tumour was serous cystadenoma (58.1%). Surface epithelial tumors were the commonest tumors (64%) followed by germ cell tumors (29%). Conclusions: A variety of benign and malignant tumours of ovary were reported in this study. Early diagnosis and appropriate treatment of ovarian neoplasms favour the good prognosis. Most common benign tumour encountered in this study was serous cystadenoma.